Crystal Plasticity Model Analysis of the Effect of Short-Range Order on Strength-Plasticity of Medium Entropy Alloys - Chen Li; Fuhua Cao; Yan Chen; Haiying Wang; Lanhong Dai (Metals, 2022)
Numerous studies have demonstrated the widespread presence of chemical short-range order (SRO) in medium and high entropy alloys (M/HEAs). However, the mechanism of their influence on macroscopic mechanical behavior remains to be understood. In this paper, we propose a novel dislocation-based model of crystal plasticity, by considering both the dislocation blocking and coplanar slip induced by SRO. The effect of SRO on the plastic deformation of CoCrNi MEAs was investigated. We found that the yield strength increases monotonically with increasing SRO-induced slip resistance, but the elongation first appeared to increase and then decreased. Further analysis suggested that the plastic elongation is a result of the competition between grain rotation-induced deformation coordination and stress concentration, which depends on the slip resistance of the SRO.